DOES ISLAMIC FINANCIAL DEVELOPMENT MATTER TO IMPROVE STANDARD LIVABILITY? EVIDENCE FROM INDONESIA - Furwanti, Reni; Lestari, Dini Maulana; Solikhin, Iin; Hardiyono, Hardiyono (Jurnal Ilmiah Ekonomi Bisnis, 2024)
This research aims to examine and analyze the relationship between Islamic financial development and Indonesia's standard of livability from an Islamic perspective. This is considered significant because, as a developing country, it is crucial for Indonesia to sustain high economic growth along with a good standard of livability. This is a quantitative study using a panel data regression method, utilizing panel data such as Islamic financing disbursement and real expenditure per capita across 33 provinces in Indonesia from 2017 to 2022. The results revealed that Islamic financial development plays a significant role in improving the standard of livability. Moreover, these findings will help understand the role of financial inclusion in sustainable development, contributing to discussions on financial and distribution policies for lower-income groups.